2016
DOI: 10.3390/ijerph13121246
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter in Urban Environments: A Trigger of Respiratory Symptoms in Sensitive Children

Abstract: The overall objective of this research was to study children’s respiratory illness levels in Targoviste (Romania) in relationship to the outdoor concentrations of airborne particulate matter with an aerodynamic diameter below 2.5 µm (PM2.5). We monitored and analysed the PM2.5 concentrations according to a complex experimental protocol. The health trial was conducted over three months (October–December 2015) and required the active cooperation of the children’s parents to monitor carefully the respiratory symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…Multiple factors, including air pollution, are contributing to increased asthma morbidity. Recent studies performed in two Romanian cities indicated that the prevalence of asthma in children is increasing at a rate of 8-11% per year [19].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors, including air pollution, are contributing to increased asthma morbidity. Recent studies performed in two Romanian cities indicated that the prevalence of asthma in children is increasing at a rate of 8-11% per year [19].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, various microenvironments are occurring at city level making difficult the conventional measurements of air quality in view of insuring a global covering of the city at spatial level. Thus, the forecasting of potential pollution episodes in a specific microenvironment and their associated health effects are also problematic [10]. One solution could be the integration of VGI component by encouraging the citizens to contribute with quasi-empirical georeferenced data e.g., GPS tracks, heart rates, street pictures, physical symptoms, respiratory events, visual observations of emissions.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, PM 2.5 forecasting accuracy is dependent on the availability and precision of the meteorological data, inventory of emissions, and chemical reaction schemes required to configure optimally the model running conditions. The forecasting of a pollution episode requires supplemental details about PM 2.5 constituents, or potential emission source to elaborate proper recommendations to the public in relation to possible health effects or to support effective measures to reduce emissions, which contributed to the episode [10].…”
Section: Dispersion Modelingmentioning
confidence: 99%
“…In the RokidAIR webbased GIS, the georeferenced layers allowed the spatiotemporal characterization of vulnerable areas in each city through the application of geospatial analysis. Medical database and receptor database were supplemented with specific information to identify the CAs that are under a major PM 2.5 impact [17,26]. The subsequent ranking of the CAs allowed the selection of the locations for the deployment of the micro-stations in Phase II.…”
Section: Methodologies and Implementationmentioning
confidence: 99%